Ownership structure, investment, and the corporate value: An empirical analysis - Cho, Myeong-Hyeon (Journal of Financial Economics, 1998)
This paper examines the relation among ownership structure, investment, and corporate value, focusing on whether ownership structure affects investment. Ordinary least squares regression results suggest that ownership structure affects investment and, therefore, corporate value. However, simultaneous regression results indicate that the endogeneity of ownership may affect these inferences, suggesting that investment affects corporate value which, in turn, affects ownership structure. The evidence shows that corporate value affects ownership structure, but not vice versa. These findings raise questions regarding the assumption that ownership structure is exogenously determined, and bring into question the results in studies that treat ownership structure as exogenous.